Optimizing targeting strategies for lithotripsy through in-vitro and in vivo studies with consideration of respiratory regularity - Sung Yong Cho; Hyeji Park; Jae Suk Park; Seong Chan Kim; Oh bin Kwon; Hyun jae Song; Min Joo Choi (BMC Urology, 2024)
Abstract Background This work aimed to identify a method to achieve improved stone targeting and safety in shockwave lithotripsy by accounting for respiration. Methods We set up an electromotive device simulating renal movement during respiration to place artificial stones within the phantom gel, measuring stone weight changes before and after shockwave exposure and the cavitation damage. We conducted clinical trials using respiratory masks and sensors to monitor and analyze patient respiration during shockwave lithotripsy. Results The in vitro efficiency of lithotripsy was higher when adjusted for respiration than when respiration was not adjusted for. Slow respiration showed the best efficiency with higher hit rates when not adjusted for respiration. Cavitation damage was also lowest during slow respiration. The clinical study included 52 patients. Respiratory regularity was maintained above 90% in regular respiration. When respiration was regular, the lithotripsy rate was about 65.6%, which stayed at about 40% when respiration was irregular. During the lithotripsy, the participants experienced various events, such as sleep, taking off their masks, talking, movement, coughing, pain, nervousness, and hyperventilation. The generation of shockwaves based on respiratory regularity could reduce pain in patients. Conclusion These results suggest a more accurate lithotripsy should be performed according to respiratory regularity.